Role of Neck Circumference (NC) in Road Traffic Accidents of Commercial Bus and Truck Drivers - Gholam Hossein Halvani; Ibrahim Salmani; Amir Hossein Khoshakhlagh; Hamid Hoboubati; Nadjme Hajian; Mahdi Halvani (Shahid Sadoughi University of Medical Sciences, 2014)
Introduction: Sleepiness may predispose drivers to road traffic accidents. Obstructive Sleep Apnea Syndrome is the most common medical cause of sleepiness. Hence increased neck circumference (NC) and obesity are known as obstructive sleep apnea syndrome risk factors. This study was conducted to assess OSAS role in occurrence of road traffic accidents in sleeping drivers of commercial heavy vehicles. Materials and Methods: Seven hundred sixteen truck and bus drivers randomly selected who referred to occupational medicine clinic for routine annual examination. In addition, drivers who had one road accident during study period consists case and other drivers consists control group, respectively. Subjects also completed demographic and driving variables (e.g. type of vehicles ...) and Epworth Sleepiness Scale questionnaire. We measured Neck Circumference and chance of road accident by Receiver Operating Characteristic Curve (ROC). Results: Mean of NC in sleepy drivers and drivers who had road accidents was significantly higher than other drivers (P< 0.05). Drivers who had night driving had significantly higher road accident in compare with others (odds: 3.83; CI: 1.36-10.77; P=0.01). Marital status (P< 0.05) and road accident (P< 0.001) had significant association with sleepiness occurrence. According to ROC curve analysis, 43.18 centimeters as cut off point for positive results, was higher sensitivity and specificity for prediction of road accidents. Conclusions: Drivers who have sleepiness and especially OSAS have more chance to involve an accident. By measuring of NC as OSAS, predictor may be able to reduce the risk of road accidents between commercial drivers.